Advancements in Waste Management Technologies: Circular Economy Approaches for Effective Waste Reduction and Resource Recovery - Alfi Rochmi; Teti Marlina; Astuti Prihatiningsih (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. The rapid increase in global waste generation has intensified environmental degradation, resource depletion, and public health risks, highlighting the urgent need for more effective and sustainable waste management systems. Conventional linear waste management approaches have proven insufficient in addressing these challenges, thereby accelerating interest in circular economy frameworks that emphasize waste reduction, reuse, and resource recovery. Purpose. This study aims to analyze recent advancements in waste management technologies and evaluate their roles in supporting circular economy strategies for effective waste reduction and material recovery. Method. The research employs a qualitative–quantitative mixed-methods approach, integrating a systematic review of peer-reviewed literature, analysis of secondary statistical data, and comparative case studies of advanced waste management systems implemented in urban and industrial contexts. Results. The findings indicate that technologies such as anaerobic digestion, advanced recycling systems, waste-to-energy conversion, and digital waste monitoring significantly enhance resource recovery rates and reduce landfill dependency. The results also demonstrate that the integration of technological innovation with policy support and stakeholder collaboration strengthens the overall effectiveness of circular waste management systems. Conclusion. The study concludes that advancements in waste management technologies play a pivotal role in operationalizing circular economy principles, contributing to environmental sustainability, economic efficiency, and long-term resource security. Strategic alignment between technology, governance, and behavioral change is essential to maximize the impact of circular waste management initiatives.